Unravelling the mechanism of lithium insertion into and extraction from trirutile-type LiNiFeF6 cathode material for Li-ion batteries. Issue 32 (28th August 2015) - de Biasi, L.; Lieser, G.; Rana, J.; Indris, S.; Dräger, C.; Glatthaar, S.; Mönig, R.; Ehrenberg, H.; Schumacher, G.; Binder, J. R.; Geßwein, H.
<x xml:space="preserve">Abstract</x> For possible future application as cathode material in lithium ion batteries, the lithium insertion mechanism of trirutile-type LiNiFeF6 was investigated.